Análise e descrição do automatismo do sistema de bombeamento d’água loteamento Vivacidade - SILVA, Wellington Oliveira da (2022)
In this work, we describe several aspects of industrial automation, when intended for water pumping systems. The objective of this work is to describe the functionality of the automation implemented in a water pumping system, using programmable logic controllers, using LADDER logic. This automation system is limited to two PLC’s, connected via wireless communication, which control the electromechanical actuators and soft-starters for starting two sets of motor pumps. Here, we emphasize the use of PLCs used in the process of command, control and monitoring of the system’s equipment under study. Definitions of communication protocols, responsible for establishing a data transmission channel (via radio) between the PLCs, were addressed. Finally, during the description of the LADDER diagram, analyzes and discussions are made about the possible situations that the complete system is submitted to.